Survey of Librarians' Motivation in Writing Scientific Papers during the COVID-19 Pandemic: A Case Study - Pambayun, Kuncoro Galih (Indonesian Journal of Librarianship, 2022)
Background: The creation of scientific papers is the main job of librarians, who are often neglected due to busy technical work. During the COVID-19 pandemic, the Work From Home (WFH) policy provided librarians with more free time to write scientific papers. Objective: This study aimed to determine the motivation of librarians on the Whatsapp Group "Pustakawan se-Indonesia Jilid II" in writing scientific papers during the COVID-19 pandemic. Method: The survey method was employed with a descriptive approach, using a sample of 61 from a total population of 256 persons within an 8-month study period in April-November 2020. This study was conducted when the Indonesian government was aggressively implementing the WFH and Large-Scale Social Restrictions (PSBB) policies. Results: The results showed that the highest motivation for librarians in writing scientific papers during the COVID-19 pandemic was sharing ideas and achieving higher credit or career scores at 64% and 59%, respectively. Although financial rewards were the lowest-ranked motive at 13%, they were the biggest encouragement for contract librarians to write scientific papers because of increased income. Job demands were the highest motivation for librarians in the writing/publication field, while scientific writing workshops were the highest contributing factor, followed by support from institutions, leaders, colleagues, and family. Meanwhile, the lack of free time was the biggest barrier to writing at 47.5%. Conclusion: The motivation of librarians in writing scientific papers during the pandemic includes sharing ideas, obtaining credit/career scores, self-actualization, hobbies/aspirations, improving library and information science, job demands, self-esteem/prestige, and financial rewards. Keywords: COVID-19; Librarian; Writing Motivation; Scientific Papers